Analysis of Occupational Safety Risk Management and Workload on Occupational Risks for Mechanics at a Workshop in Kwala Bingai, Stabat District - Muhammad Farid Abrar; Waizul Qarni; Nur Ahmadi Bi Rahmani (JEM17: Jurnal Ekonomi Manajemen, 2026)
This research endeavors to investigate the influence of occupational safety protocols and task volume on the inherent hazards encountered by motorcycle mechanics situated in KwalaBingai, within the Stabat District. The study adopted a quantitative survey methodology, engaging a sample of 50 mechanics. Information was systematically gathered through a structured questionnaire and subsequently subjected to a range of statistical analyses. These analyses encompassed tests for validity and reliability, an evaluation of classical assumptions, and the application of multiple linear regression techniques. The findings indicate that workplace safety and workload have a significant influence on the occupational risks faced by mechanics. Good safety practices are associated with lower occupational risks, while higher workloads increase the likelihood of workplace hazards. Furthermore, these two variables jointly influence the level of occupational risk experienced by mechanics. This study concludes that improving workplace safety and maintaining a balanced workload are crucial for reducing occupational risks in motorcycle repair shops. These findings are expected to assist shop owners in creating a safer and more effective work environment. Keywords : Work Safety, Workload, Work Risk.